Gestational Diabetes Mellitus: Impact of Maternal Blood Sugar Level and BMI on Foetal Birth Weight - Deka, Dr. Bipul Prasad; Begum, Dr. Dimpy (International Journal of Innovative Research in Medical Science, 2019)
Gestational diabetes mellitus (GDM) is defined as glucose intolerance of variable degrees with an onset, or first recognized, during pregnancy. About 15-45% of babies born to diabetic mothers can have macrosomia. This prospective case control study was conducted in the department of Obstetrics and Gynaecology of Gauhati medical college and hospital, Guwahati, Assam during the period of 2013-2015. A total of 160 patients were included in the study. 100 patients without any glucose abnormality were taken as control and 60 patients with gestational diabetes mellitus were included in the study as cases. In this study it was found that mean birth weight in GDM cases is more than normoglycemic control. The overweight and obesity group (BMI>25) have maximum birth weight. In this study it was found that the fasting blood glucose level is maximum in mothers with baby birth weight >3.5 kg.